Modelling and Optimizing Process Parameters of AISI D2 Tool Steel for WEDM automation. Issue 1 (December 2020) - Kumar, Aneesh
Abstract: The AISI D2 tool steel are the material that for machining of heat treated AISI D2 tool steel, a highly developed method must be employed. Due to exceptional thermo-mechanical properties and superior wear resistance AISI D2 tool steel are finding widespread applications in a lot of manufacturing industries. WEDM is one of the highly developed and sophisticated methods for making of intricate shapes and convoluted details as required for dies and punches. For efficient machining, the need of optimization and appropriate choices of process parameters such as Material Removal Rate and Surface Roughness is utmost goal.